GHIBAH DAN NAMIMAH - Muhammad Rasyid; Norlaila Norlaila (Berajah Journal, 2026)
This study examines the phenomena of ghibah and namimah as destructive behaviors from an Islamic perspective, focusing on their definitions, Islamic legal justifications, and their social, psychological, and spiritual impacts, as well as prevention strategies based on moral education and digital literacy. Using a qualitative descriptive literature review method, the findings indicate that ghibah—speaking ill of someone’s faults—and namimah—sowing discord—disrupt social harmony, diminish the quality of faith, and may hinder entry into Paradise, particularly in the era of social media, which accelerates their spread. Effective prevention is achieved through verbal guidance, piety, and a culture of self-reflection, with practical implications for education, family, and society. This research contributes to strengthening noble ethics in the face of modern social dynamics.